Compositional Analysis and Development of Jam, Jelly and Squash from Strawberry Cultivated in Bangladesh (Revised) (Journal of Environmental Science and Natural Resources, 2015)
16th February 2015. Due to a number of missing tables and figures, this article (DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22182) was withdrawn from Vol.7(1) and has been republished with corrections in Vol.7(2) pp.185-190 (DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22230).The EditorAbstract:The Strawberry was collected from Rajshahi and the pulp was extracted. Then the pulp was analyzed for proximate composition. The proximate analysis of Strawberry pulp showed 91.91% moisture, 11.5% TSS, 3.50% reducing sugar, 2.50% non-reducing sugar, 6.00% total sugar, 0.36% ash, 2.80% pH, 1.12%acidity and 50.90mg/100g vitamin-C. A total three types of products with 3 different formulations were prepared and packed in appropriate containers for storage studies. Products were stored at room temperature and changes during storage were observed at an interval of 30 days for a period of 4 months. A taste panel consisting of 10 panelists studied the acceptability of the samples. The consumers preferences were measured by statistical analysis of the scores obtain from the response of the test panel. Among the products three samples of jam, jelly and squash were awarded the highest scores by the panelists; C2 (Jam: TSS-67%, Pectin-0.5%, pH-3.2%), D2(TSS-67%, pectin-0.5%, pH-3.2%) and E3 (squash: TSS-40%, Juice 25%, acidity-1.25%, KMS-350mg/kg ). DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22230 J. Environ. Sci. & Natural Resources, 7(2): 185-190 2014